Pueden considerarse significativas las reformas fiscales de México? - Sergio Lagunas Puls; Julio César Ramírez Pacheco (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2016)
– It is the purpose of this work to analyze the significance of changes in average for the collection of value-added (VAT) and income taxes from year 2000 and up to the second quarter of 2015. To accomplish that, classic methods of significance will be applied, but contrasted with tests for the typified difference of the average, fundamental parameters of the meta-analysis Cohen's Delta. The main conclusions are that although there have been relevant changes in the tax collection process such as limits in the tax consolidation regime, complementary taxes e.g., flat rate business tax, substitute tax credit to wages, tax on cash deposits and the standardization of the VAT to 16%, there is no strong evidence to state an efficient national tax collection system.
Keywords: H21; M41; M48; 330; tax collection; tax reform; changes in value-added and income taxes; significance levels